Cultural Heritage and Regional Tourism Development in Yunnan, China - Bai, Jie; Johar, Suhana Binti; Mohammad, Noraziah Binti (Journal of Ecohumanism, 2024)
This study explores the relationship between cultural heritage and regional tourism development in Yunnan. The provincial government has initiated efforts to save and conserve the cultural heritage of its many ethnic communities. With the preservation, the government is also building the tourism industry. In order to achieve a harmonious equilibrium between economic advantages and the safeguarding of cultural treasures, it is imperative for all stakeholders to engage in meticulous and deliberate deliberations. This research therefore seeks to comprehensively explores Yunnan’s experience with the goal of elucidating the mechanisms via which cultural heritage influences tourism and, reciprocally, how tourism influences the perception and preservation of cultural heritage. The research indicates that there is a distinction between national and regional officials efforts in spearheading the direction of tourism development.. The long-term impact of the subject under consideration will be contingent upon its ability to effectively integrate preservation initiatives with sustainable development.